Age determination of Glen Torridon peat core from Wales - Anderson, David E (PANGAEA, 2021)
14C and 210Pb age determination of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.
Keywords: C-PEAT; Peatland